2016
DOI: 10.5812/jjm.39121
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of AmpC β-lactamase in Clinical Isolates of Escherichia coli, Klebsiella spp., and Proteus mirabilis in a Tertiary Hospital in Tehran, Iran

Abstract: Background: AmpC β-lactamase confers resistance to a variety of β-lactam agents, and all plasmid-mediated AmpC genes are con-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 13 publications
1
15
0
Order By: Relevance
“…Also, according to the PCR assay results, we found the prevalence of AmpC genes in 35.3% AmpCproducing isolates. The result was consistent with those of the studies carried by Saffar et al (5) and Fam et al (26) from Egypt where AmpC prevalence was 15.83% and 28.3%, respectively. On the other hand, the base on the geographical location, the species studied, the period of study, the prevalence, and type of acquired plasmid AmpC detected can be different(27).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Also, according to the PCR assay results, we found the prevalence of AmpC genes in 35.3% AmpCproducing isolates. The result was consistent with those of the studies carried by Saffar et al (5) and Fam et al (26) from Egypt where AmpC prevalence was 15.83% and 28.3%, respectively. On the other hand, the base on the geographical location, the species studied, the period of study, the prevalence, and type of acquired plasmid AmpC detected can be different(27).…”
Section: Discussionsupporting
confidence: 93%
“…Importantly, Amp C is a major clinical concern since these enzymes play a signi cant role in conferring cephamycins hydrolyze and also are able to increase the minimum inhibitory concentration (MIC) value of carbapenems (3,4). ESBLs and AmpC βlactamases production can be chromosomal or plasmid-mediated and can be spread by horizontal transfer between gram-negative bacteria members (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…They reported that 13 (3.3%) isolates were identified as AmpC producers, which 11 of the 13 isolates contained the bla CMY gene. In another survey performed by Saffar et al [24] in Iran (Tehran), bla DHA gene was detected in 14.8% isolates of E. coli. Their results confirmed this hypothesis that geographical location plays the most important role in the distribution of bla DHA gene, due to the closer regions have a relatively similar distribution of bla DHA gene [24].…”
Section: Discussionmentioning
confidence: 92%
“…In another survey performed by Saffar et al [24] in Iran (Tehran), bla DHA gene was detected in 14.8% isolates of E. coli. Their results confirmed this hypothesis that geographical location plays the most important role in the distribution of bla DHA gene, due to the closer regions have a relatively similar distribution of bla DHA gene [24]. Recently, plasmid-mediated quinolone resistance determinants have been also reported among E. coli isolates, furthermore, plasmid-mediated fosfomycin-modifying enzymes, fosA3 and fosC2, were identified in E. coli clinical isolates.…”
Section: Discussionmentioning
confidence: 92%
“…Antimicrobial agents can greatly contribute to the clinical control of UTI. Antimicrobial resistance, in particular, multidrug-resistant Gram-negative bacilli, has posed a remarkable challenge for the clinical settings ( Saffar et al., 2016 ). Diverse drug resistance mechanisms have been introduced in Gram-negative bacteria among which, extended-spectrum β-lactamases (ESBL) production, AmpC β-lactamase generation, efflux, and porin deficiency can be mentioned.…”
Section: Introductionmentioning
confidence: 99%